(untitled) (EU and comparative law issues and challenges series (ECLIC), 2021)
The debate about the “just price” has ancient origin and returns forcefully to the scene when, in the event of crises of various kinds, there is a rapid and significant increase in prices of given goods or services. In this article it is examined the problem of whether price increases of such a nature could, or should, be considered illicit under EU competition law. The central part of the article reviews different theories on what a “just price” should be and focuses on the idea that a price is “just” when it functions as index of relative scarcity in free markets. It is claimed that such a function deserves protection by EU law. Therefore, price adjustments in response to shocks cannot and should not be considered illegal: it is unacceptable to sanction private firms by attributing them the wrong of not having substituted, at their own expense, for the exercise of a public function (that of making sure that price increases do not put at risk solidarity and other constitutional principles).